Pengaruh Lama Penyimpanan Susu Kedelai dalam Lemari Es Terhadap Pertumbuhan Bakteri Psikrofilik - Bayu Nur Khotib; Yuliana Prasetyaningsih; Fitri Nadifah (LPPM STIKES Guna Bangsa, 2015)
Background: Soy milk is a drink with full of nutrients, especially contains high protein and vitamin. In room’s temperature, soy milk easy to be damage because of bacterial’s activity. Storaging in low temperature is one of control effort to prevent damaging in soy milk. Research Purpose: To find out whether there is influence of soy milk long-time storaging in refrigator toward bacterial psychrophilic’s growth. Research methods: Methods which use in this research is quasi experimental with pre and post test with control design program. Intervention to sample is storaging the sample in refrigator during 1 until 5 days. Results: Data results obtained from this research was the highest number of colony’s growth occured in days 3 with 4733,33 CFU/ml and that number not exceed yet the bacterial pollution number based on soy milk SNI that is 1 x 106. Conclusion: There was influence of soy milk long-time storaging in refrigator toward bacterial psychrophilic’s growth.